ANALISIS SISTEM BAGI HASIL PAAMBI’ MENGGUNAKAN KONSEP MUDHARABAH PETERNAKAN SAPI - Muhammad Nasri Katman; Syamsul Maarif; Muslimin Kara; Muhammad Nur; Trisno Wardy Putra (Universitas Kuningan, 2022)
AbstractThis study aims to determine the Paambi profit sharing system between cattle owners and breeders using the concept of mudharabah cattle farming in Tanjung Lalak Utara Village, Kab. New city. This type of research is descriptive qualitative by providing an overview of events, background observations, actions, and discussions that are directly related to the profit-sharing system between cattle owners and farmers using mudharabah in Tanjung Lalak Utara Village. The results showed the concept of profit sharing using a trust system orally without a time limit agreement and ended with an average distribution of 50:50 and losses were resolved by deliberation. Submission of capital is in the form of cash, but also there is no capital in the form of goods (cows) which is prohibited by the fuqaha because the estimated price of the goods is uncertain and can result in uncertainty (gharar) of the amount of mudharabah capital. However, the Hanafi school of thought allows it with a note that the value of the goods used as capital has been obeyed at the time of the contract by the shahibul maal and mudharib. The period of cooperation is also not limited, causing confusion between the two parties. This kind of thing is contrary to the cooperation of mu'amalah (mudharabah) which must be clear and not contain uncertainty. However, this profit-sharing system does not cause any party to be wronged because the distribution is balanced and does not harm one party.Keywords: Paambi' Profit Sharing System, Mudharabah, Cattle FarmAbstrakPenelitian ini bertujuan untuk mengetahui sistem bagi hasil paambi’ antara pemilik sapi dengan pihak peternak menggunakan konsep mudharabah peternakan sapi di Desa Tanjung Lalak Utara Kab. Kota Baru. Jenis penelitian ini adalah kualitatif deskriptif dengan memberi gambaran terkait kejadian, latar pengamatan, tindakan, orang dan pembicaraan yang berkaitan langsung dengan sistem bagi hasil antara pemilik sapi dengan pihak peternak menggunakan konsep mudharabah pada Desa Tanjung Lalak Utara. Hasil penelitian menunjukkan konsep bagi hasil menggunakan sistem kepercayaan secara lisan tanpa perjanjian batas waktu dan diakhiri rata-rata pembagian 50:50 serta kerugian diselesaikan secara musyawarah. Penyerahan modal awal tidak hanya berupa uang tunai, melainkan juga penyerahan modal dalam bentuk barang (sapi perekor) yang mana fuqaha melarangnya karena barang tidak dapat dipastikan taksiran harganya dan dapat mengakibatkan ketidakpastian (gharar) besarnya modal mudharabah. Namun para ulama mazhab hanafi membolehkannya dengan catatan nilai barang yang dijadikan modal telah di sepakati pada saat akad oleh shahibul maal dan mudharib. Jangka waktu kerjasama juga tidak dibatasi sehingga menimbulkan ketidakjelasan diantara kedua belah pihak. Sehingga dianggap bertentangan dengan kerjasama mu’amalah (mudharabah) yang harus jelas dan tidak mengandung ketidakpastian. Namun sistem bagi hasil ini tidak merugikan satu pihak karena pembagiannya seimbangKata Kunci: Sistem Bagi Hasil Paambi’, Mudharabah, Peternakan Sapi